النظم الرعوية المستدامة لتعزيز خدمات النظام البيئي في تونس - Hassan, Sawsan; Louhaichi, Mounir; Jamel, Kailene (International Center for Agricultural Research in the Dry Areas, 2024)
The presentation was delivered by Sawsan Hassan as part of the Scientific Symposium on the Inventory of Forests and Rangelands in Tunisia and the Restoration System in Sbaihia, Zaghouan. Held on May 16, 2024, the presentation emphasized the integration of sustainable pastoral practices to improve ecosystem services, aligning with ongoing restoration efforts in the region.